2021
DOI: 10.22175/mmb.10963
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Smoked Beef Brisket Palatability from Three USDA Quality Grades

Abstract: The objective of this study was to investigate differences in smoked beef brisket palatability from 3 USDA quality grades (USDA Prime, average [middle 1/3] Choice, and Select). Briskets (n = 54; 18 per quality grade) were seasoned with a blend of 1:1 coarse salt/black pepper, and then cooked in a smoker to a final internal temperature of 93°C for approximately 6 to 7 h. For sensory analysis, briskets were separated into point (pectoralis superficialis) and flat (pectoralis profundus) portions and then sliced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The "low and slow" cooking method, which we refer to as BBQ-ing, is typically the preferred cooking style for primal cuts of inexpensive and undesirable meat due to their toughness (Jeremiah et al, 2003;Harris et al, 2017). Low and slow cooking can transform these cuts from being tough to a tender finished product (Jeremiah et al, 2003;Harris et al, 2017;Fletcher et al, 2021). Using a sensory panel, Harris et al (2017) showed that BBQ-ing beef brisket increases consumer palatability in terms of juiciness and tenderness when the meat is cooked low and slow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The "low and slow" cooking method, which we refer to as BBQ-ing, is typically the preferred cooking style for primal cuts of inexpensive and undesirable meat due to their toughness (Jeremiah et al, 2003;Harris et al, 2017). Low and slow cooking can transform these cuts from being tough to a tender finished product (Jeremiah et al, 2003;Harris et al, 2017;Fletcher et al, 2021). Using a sensory panel, Harris et al (2017) showed that BBQ-ing beef brisket increases consumer palatability in terms of juiciness and tenderness when the meat is cooked low and slow.…”
Section: Introductionmentioning
confidence: 99%
“…Using a sensory panel, Harris et al (2017) showed that BBQ-ing beef brisket increases consumer palatability in terms of juiciness and tenderness when the meat is cooked low and slow. This cooking methods adds value to underutilized muscle of the beef carcass (Jeremiah et al, 2003;Harris et al, 2017;Nyquist et al, 2018;Fletcher et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The use of electronic devices equipped with sensory software or digital ballots has emerged as a more efficient means of collecting and compiling data from sensory trials. Several researchers have used digital ballots through Qualtrics Software Survey (Qualtrics, Provo, UT) to collect sensory data of cooked meat samples from trained panelists (McKillip et al, 2018;Vierck et al, 2018;Ponce et al, 2019) and untrained consumer panelists (Morrow et al, 2019;Sepulveda et al, 2019;Fletcher et al, 2021).…”
Section: Introductionmentioning
confidence: 99%